Indoor Radon Measurement in Patras Region Using Activated Carbon - Kaplanis, S. N.; Bakalis, A. N. (HNPS Advances in Nuclear Physics, 2020)
Measurements of Rn concentration in air indoors in Patras area, Greece, have been carried out and are presented in this paper. The method used is based on George method using activated Carbon which adsorbs Rn and a Nal (TI) γ-ray detector. The method determines the γ-ray activity of the Rn decay products. The Rn level in (pCi/l) and the total error are presented for different geological areas in the region.